Association between fluid overload and delirium/coma in mechanically ventilated patients. Issue 1 (15th April 2020) - Ouchi, Akira; Sakuramoto, Hideaki; Hoshino, Haruhiko; Matsuishi, Yujiro; Sakaguchi, Tatsuya; Enomoto, Yuki; Hoshino, Tetsuya; Shimojo, Nobutake; Inoue, Yoshiaki
Abstract : Aim: Several studies have shown an association between fluid overload (FO) and mortality or duration of mechanical ventilation in critically ill patients. However, the association between FO and delirium duration remains unclear. Methods: This retrospective observational cohort study was undertaken at University of Tsukuba Hospital (Tsukuba, Japan) from April 2015 to March 2017. Mechanically ventilated patients who stayed in the intensive care unit for more than 7 days were eligible for inclusion. Univariate analysis was carried out with the Mann–Whitney U ‐test for continuous variables and Fisher's exact test for categorical variables. A multivariate proportional odds logistic regression model was used to evaluate the association between FO and delirium/coma days (DCDs) during the 7‐day study period. Results: A total of 118 patients were included and divided into FO and non‐FO groups. Fluid overload occurred in 40% of patients. The FO group had a higher APACHE II score than the non‐FO group (19 [16–26] versus 23 [20–29], P = 0.017). Cumulative fluid balance at day 3 was higher in the FO group (3, 238 [281–6, 530] versus 7, 886 [4, 106–10, 631], P < 0.001). Delirium days within 7 days was longer in the FO group (1 [0–3] versus 2 [1–3], P = 0.048) and DCDs was longer in the FO group (4 [1–5] versus 6 [3–7], P = 0.002). After adjusting for covariates, there were significant associations between FO and DCDs (odds ratio, 2.16; 95% confidence interval, 1.05–4.47). Conclusions: Our findings suggest that FO is associated with increased DCDs in mechanically ventilated patients. Abstract : This retrospective observational cohort study was undertaken to reveal the association between fluid overload and delirium duration. Our findings suggest that fluid overload is associated with increased delirium/coma days in mechanically ventilated patients.